Uncovering the mechanical behavior of twisted carbon nanotube assemblies under high-speed stretching. (December 2021) - Hu, Xiaoping; Zheng, Yuxuan; Wang, Deya; Sun, Gengzhi; Zhang, Xiaohua; Tian, Jie; Wang, Pengfei; Xu, Songlin; Zhou, Fenghua
Abstract: Twisted carbon nanotube (CNT) fibers are regarded as an effective assembly for intelligent actuators and artificial muscles, which are inevitable to encounter high-speed collision and impact. In order to reveal the dependence of high-speed mechanical performance on the CNT assembly, the dynamic failure behaviors of untwisted and twisted CNT assemblies under instant stretching are investigated with experimental and numerical methods. The strength of the untwisted and loosely-packed CNT ribbon is more sensitive to strain-rate than densified and twisted CNT fiber owing to its interlaced CNT network. The numerical results demonstrated that the evolution of interior flaws governed the mechanical behavior under different stretching rates. The instant stretching does not allow an efficient stress distribution within the limited time, and thus hinders the flaw evolution, leading to the cascade-like failure mode and a strain-rate hardening effect. It is inferred that the rate-dependent sensitivity may be attributed to the twisted microstructure and untwisted CNT ribbon. This work on the dynamic behavior of twisted CNT ribbon/fiber can help to design the twisted structure under the high-speed applications. Graphical abstract: Image 1 Highlights: Dynamic and in-situ SEM experimental results show the different failure modes of twisted CNT fiber. The increasing of strain rate inclines to decrease the failure strain and increase the strength of CNT assemblies. Rate-dependent sensitivity of CNT assembly attributed to the untwisted ribbon and twist-geometry properties. The shrinking axial displacement along the twisting process inclines to increase the ductility of twist fiber.